2014
DOI: 10.1371/journal.pone.0088692
|View full text |Cite|
|
Sign up to set email alerts
|

Manual Control Age and Sex Differences in 4 to 11 Year Old Children

Abstract: To what degree does being male or female influence the development of manual skills in pre-pubescent children? This question is important because of the emphasis placed on developing important new manual skills during this period of a child's education (e.g. writing, drawing, using computers). We investigated age and sex-differences in the ability of 422 children to control a handheld stylus. A task battery deployed using tablet PC technology presented interactive visual targets on a computer screen whilst sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
70
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 58 publications
9
70
3
1
Order By: Relevance
“…However, for the individual MD test items, it was found that boys outperformed girls on the MD1 item, whereas girls outperformed boys on the MD2 item. Since better manual skills have been more often mentioned for girls (Flatters et al, 2014;Livesey et al, 2007;Sigmundsson & Rostoft, 2003), it is surprising that better performance has not been confirmed for girls in test items MD1 and MD3. Generally, higher manual skills performance in girls has often been attributed to the early interest of girls in activities including fine motor skills (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the individual MD test items, it was found that boys outperformed girls on the MD1 item, whereas girls outperformed boys on the MD2 item. Since better manual skills have been more often mentioned for girls (Flatters et al, 2014;Livesey et al, 2007;Sigmundsson & Rostoft, 2003), it is surprising that better performance has not been confirmed for girls in test items MD1 and MD3. Generally, higher manual skills performance in girls has often been attributed to the early interest of girls in activities including fine motor skills (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, girls' locomotor proficiency has more often been reported as higher than boys (Barnett, Morgan, van Beurden, & Beard, 2008;Hardy et al, 2009;van Beurden, Zask, Barnett, & Dietrich, 2002). Most studies focused on balance or fine motor skills have found better results in girls (Flatters, Hill, Williams, Barber, & Mon-Williams, 2014;Livesey et al, 2007;Sigmundsson & Rostoft, 2003;Venetsanou & Kambas, 2011;Vlachos, Papadimitrou, & Bonoti, 2014), or have not revealed any significant gender differences (Shala, 2009;Singh et al, 2015;Van Waelvelde, Peersman, Lenoir, Smits Engelsman, & Henderson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a relevant scientific issue -in what way the needs of children should be considered, the diversity of methods and means should be applied and sports training programmes for juvenile dancers should be modelled in order to encourage the expression of their sport motivation. Taking into account these things, a hypothesis is raised in the work that the sports training model for junior (9)(10)(11) dancers that is based on the athlete's management theory accentuating the significance of the feedback strengthens the sport motivation [15,16].…”
Section: Pedagogics Psychologymentioning
confidence: 99%
“…Analysing scientific references, we missed the rules of the effect of dancers' training means (contents of practice) on the sports preparedness of juvenile dancers. The researchers state that children are very active in the period of the middle childhood (9)(10)(11) and they participate willingly in such sports activities as games and relay races [7][8][9]. The researchers of dances [10][11][12] state that different dance styles with the most various moves should be applied in the initial stage of training of juvenile dancers.…”
mentioning
confidence: 99%
“…Так, в первые годы жизни девочки успешнее овладевают мелкой мото-рикой рук [17], превосходят мальчиков по вербальным способностям [18−20]. Они не отличаются от мальчиков по скорости овладения речью, но начинают раньше гово-рить, при этом их речь более правильная и сложная [21].…”
unclassified